Estudo dos indicadores de qualidade do solo para recuperação de nascentes em região de cerrado mineiro - Reisila Simone Migliorini Mendes (2017)
The water crisis that we are experiencing in recent years is currently a great threat posed over the humanity. This crisis has been attributed to the rainfall deficit, what would compromise the aquifers and springs. Although, the vitality of the aquifers and springs does not depend only on rainfall, but also of the soil use. The main impact problems generator, such as loss of springs, aquifer impairment and rainfall deficit are related to the loss of forests in riparian zones and in areas of water recharge. The vegetation, through the evapotranspiration, establishes the links between a groundwater and the atmospheric water. Due to evapotranspiration, we have rainfall that supplies the springs, rise the soil water level that supplies the rivers and water available to living things. Thus, the restoration of water springs depends on the correct establishment of vegetation to fulfill the mentioned functions. The suitable vegetation not only develop hydrological cycle through evaporation, but also allows drainage and infiltration of surface water to the and groundwater and the inverse, capillarity of groundwater to the surface. The effectiveness of this system ensure the water availability in all seasons, in an equitable manner. In the present work, have been proposed the recovery of a spring degraded by pasture with the planting of native plantings from the Cerrado through the system of zoning buffer riparian vegetation. The recovery was evaluated after one year through soil quality indicators to water springs, such as establishment of the vegetation, water flow, soil water content, macro and microporosity of deformed samples and soil fertility of deformed samples. These results were compared with a spring area revovered ten years ago. The results revealed that the mains impact on the water spring under study was the loss of soil macroporosity, which has compromised the drainage. This impact was caused by the low organic content of the soil generated by the vegetable absence. To the contrary, the recovered spring showed a lot of organic matter content which it was correlated to the porosity, soil water content and water flow estimated in 0,5 L/s. It concludes that correct handling of the water spring area, established by the monitoring of quality soil indicators, essential for the success of this recuperation. The recovery target in study is the soil microporosity reduction by planting biomass producers species.